Comeback Evolution : Selected Works of Walter K. Delbridge - Delbridge, Walter K., 1946- (Book collections on Project MUSE., 2022)
"A compelling foray into the life and work of poet philosopher Walter K. Delbridge. From rising star of the civil rights era to outcast 'schizophrenic,' Delbridge reclaims his dignity in poetry and prose, constructing beauty from fragmented structures of oppression. Living a life of relative isolation, he determined to 'steel' his mind through study and creative expression, building inner pathways of resilience that would lead to his recovery and return, on his terms this time. From stargazing poetry to his call for free thinkers to join him in writing the "Book of Ideas," to intimate journal entries dating back to 1982, Delbridge reveals the transformative power of his own experience, inspiring others to join him in the dance. As Delbridge's longtime collaborator Kate Tucker says, "His life, his experience is his great work, so great that it takes a whole choir of voices to sing it." Tucker's voice infuses the book with biographical context and editorial commentary in a subtle duet with Delbridge's own special kind of jazz"--